2019
DOI: 10.1038/s41598-019-51222-9
|View full text |Cite
|
Sign up to set email alerts
|

Recreational vessels without Automatic Identification System (AIS) dominate anthropogenic noise contributions to a shallow water soundscape

Abstract: Recreational boating is an increasing activity in coastal areas and its spatiotemporal overlap with key habitats of marine species pose a risk for negative noise impacts. Yet, recreational vessels are currently unaccounted for in vessel noise models using Automatic Identification System (AIS) data. Here we conduct a case study investigating noise contributions from vessels with and without AIS (non-AIS) in a shallow coastal area within the Inner Danish waters. By tracking vessels with theodolite and AIS, while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(53 citation statements)
references
References 38 publications
0
53
0
Order By: Relevance
“…However, AIS transmitters are only required on larger ships, passenger vessels and large fishing vessels. Thus, millions of recreational vessels worldwide are not required to have an AIS, which makes it difficult to develop AIS-based models (Hermannsen et al, 2019). Despite this issue, it is clear that in the future, NIS Invasion Threat Scores should include recreational vessel traffic data from surrounding marinas when estimating a specific port's ITS and predicted scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…However, AIS transmitters are only required on larger ships, passenger vessels and large fishing vessels. Thus, millions of recreational vessels worldwide are not required to have an AIS, which makes it difficult to develop AIS-based models (Hermannsen et al, 2019). Despite this issue, it is clear that in the future, NIS Invasion Threat Scores should include recreational vessel traffic data from surrounding marinas when estimating a specific port's ITS and predicted scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…Pleasure craft (e.g., jet skis, yachts) represent a considerable noise source in some coastal areas (Samuel et al, 2005;Haviland-Howell et al, 2007). Hermannsen et al (2019) found that non-AIS recreational vessels such as speedboats and sailing vessels elevated ambient noise in the 1/3 octave bands centered at 125 Hz, 2 kHz, and 16 kHz by up to 55, 47, and 51 dB, respectively, dominating the soundscape in a coastal area and likely contributing to the disturbance of a local population of harbor porpoise. We observed a large decrease in pleasure craft occurrence in July 2020, which likely continued into the autumn as Nova Scotia extended its restrictions on social activities and visitors into that period.…”
Section: Discussionmentioning
confidence: 99%
“…For example, research on non-indigenous marine species invasions via recreational vessels in the SFB region has relied on boater questionnaires and vessel observation at local marinas (e.g., Zabin et al, 2014), leaving vessel activity on the water largely unknown. In other coastal areas with high recreational traffic, research has sought to assess the level of underwater noise pollution from these vessels through manual tracking (Erbe, 2002;Hermannsen et al, 2019). Using the M2 to collect vessel tracks would likely provide a more robust dataset than relying on physical human effort.…”
Section: Discussionmentioning
confidence: 99%